Physiological and biochemical biomarkers of macrophyte resilience to military-related toxic stressors - Tsyhanenko-Dziubenko, Illia; Kireitseva, Hanna; Fonseca, Araújo Joana (Видавництво Львівської політехніки, 2024)
This study employs state-of-the-art analytical tools to investigate the ecotoxicological impacts of mercury contamination on aquatic macrophytes in post-military zones, focusing on Typha latifolia and Lemna minor as model organisms. The research methodology integrates multiple analytical techniques: spectrophotometric chlorophyll quantification using the Holm-Wettstein method, atomic absorption spectrometry utilizing a C-115PK Selmi spectrometer (precision ±0.001 mg/L), and fluorescence analysis via Flyuorat-02-Panorama spectrofluorometer. Through this comprehensive analytical approach, we elucidated the bioaccumulation patterns and physiological responses of these hydrophytes to varying concentrations of mercury (0.35-2.0 mg/L). Results demonstrated differential bioaccumulation capacities between T. latifolia and L. minor, with the latter exhibiting higher mercury sequestration potential (0.51 mg/kg vs 0.4 mg/kg dry weight). Concentration-dependent phytotoxic effects were observed, manifesting as morphological alterations, chlorophyll degradation, and disruption of photosynthetic processes. Notably, a consistent increase in the chlorophyll b to chlorophyll a ratio was documented, indicative of selective degradation of photosystem II under mercury stress. The study further revealed the inactivation of key Calvin cycle enzymes, leading to attenuated carbon fixation and overall photosynthetic capacity. These findings not only elucidate the mechanistic underpinnings of mercury toxicity in aquatic macrophytes but also underscore their potential as bioremediators in mercury-contaminated aquatic ecosystems. The research provides critical insights for developing targeted phytoremediation strategies and ecosystem restoration protocols in post-military aquatic environments.
Keywords: environmental safety; water resources; mercury bioaccumulation; aquatic macrophytes; photosynthetic inhibition; post-military ecosystem restoration